Role of plasminogen activated inhibitor-1 in the pathogenesis of anticoagulant related nephropathy - Medipally, Ajay; Xiao, Min; Biederman, Laura; Dasgupta, Alana; Satoskar, Anjali A.; Parikh, Samir; Ivanov, Iouri; Mikhalina, Galina; Brodsky, Sergey V. (Frontiers in Nephrology, 2024)
Anticoagulant related nephropathy (ARN) is the result of glomerular hemorrhage in patients on systemic anticoagulation therapy or underlying coagulopathy. Red blood cells (RBC) that passed through the glomerular filtration barrier form RBC casts in the tubules, increase oxidative stress and result in acute tubular necrosis (ATN). The mechanisms of ARN still not completely discovered. Plasminogen activator inhibitor-1 (PAI-1) plays a significant role in the maintenance of coagulation homeostasis. We developed an animal model to study ARN in 5/6 nephrectomy (5/6NE) rats. The aim of this study was to elucidate the role of PAI-1 in the ARN pathogenesis. 5/6NE rats were treated per os with warfarin (0.75 mg/kg/day) or dabigatran (150 mg/kg/day) alone or in combination with PAI-1 antagonist TM5441 (2.5, 5.0 and 10 mg/kg/day). TM5441 in a dose dependent manner ameliorated anticoagulant-induced increase in serum creatinine in 5/6NE rats. Anticoagulant-associated increase in hematuria was no affected by TM5441. The levels of reactive oxygen species (ROS) in the kidneys were in a dose-dependent manner decreased in 5/6NE rats treated with an anticoagulant and TM5441. Our data demonstrates that PAI-1 may reduce ARN by decreasing ROS in the kidneys. Glomerular hemorrhage is not affected by anti-PAI-1 treatment. These findings indicate that while symptoms of ARN can be reduced by PAI-1 inhibition, the main pathogenesis of ARN – glomerular hemorrhage – cannot be prevented.